Rapid Isolation and Concentration of Pathogenic Fungi Using Inertial Focusing on a Chip-Based Platform - Fuchs, Beth Burgwyn; Eatemadpour, Soraya; Martel-Foley, Joseph M.; Stott, Shannon; Toner, Mehmet; Mylonakis, Eleftherios (Frontiers in Cellular and Infection Microbiology, 2019)
Systemic Candida infections remain a leading cause of nosocomial infections in the United States and worldwide. Many challenges remain in achieving rapid, direct diagnosis of fungal bloodstream infections due to limitations of conventional diagnostic methods that continue to demonstrate poor sensitivity, prolonged culture times that lead to delayed treatment, and detection variability between tests that compromises result reproducibility. Despite advancements in technology, mortality and cost of care presented by blood stream infection with Candida spp. (candidemia) continues to rise and there is an urgent need for the development of novel methods to accurately detect Candida species present within the blood. This is especially true when patients are infected with drug resistant trains of Candida where accurate and immediate therapeutic treatment is of the important. This study presents a method of separating fungal cells from lysed blood using inertial forces applied through microfluidics in order to abbreviate the time required to achieve a diagnosis by mitigating the need to grow blood cultures. We found that C. albicans can segregate into a focused stream distinct from white blood cells isolated within the Inertial Fungal Focuser (IFF) after red blood cell lysis. As a result of the focusing process, the collected cells are also concentrated 2.86 times. The same IFF device is applicable to non-albican species: Candida parapsilosis, Candida glabrata, and Candida tropicalis, providing both isolation from lysed blood and a reduction in solution volume. Thus, the devised platform provides a means to isolate medically significant fungal cells from blood and concentrate the cells for further interrogation.